TEACHER PERFORMANCE INFLUENCED BY ORGANIZATIONAL CULTURE AND JOB CHARACTERISTICS IN TEACHERS ROUDLATUN NASYIIN MOJOKERTO EAST JAVA - Elfia Nora; Immanuel Osijo Ustradi (International Journal of Economics and Management Research, 2022)
Organizational culture and job characteristics are factors that can affect teacher performance in schools. The purpose of this study is 1) to find out whether there is an influence between organizational culture on the performance of Roudlatul Nasyiin Mojokerto teachers, 2) to find out whether there is an influence between job characteristics on the performance of Roudlatul Nasyiin mojokerto teachers. The type of quantitative research, with the object of research of Roudlatul Nasyiin Mojokerto school teachers totaling 69 people, with the analysis carried out is multiple regression. The results of the study stated that there was an influence between organizational culture and the performance of Roudlatul Nasyiin Mojokerto Teachers and there was an influence between Job Characteristics on the Performance of Roudlatul Nasyiin Mojokerto teachers